2024
DOI: 10.1002/brx2.52
|View full text |Cite
|
Sign up to set email alerts
|

Prospects of antidiabetic drugs in the treatment of neurodegenerative disease

Lidan Hu,
Wenmin Wang,
Xiangjun Chen
et al.

Abstract: Neurodegenerative diseases (NDs) stand for a group of disorders characterized by the progressive loss of neurons in the brain and peripheral organs, resulting in motor and cognitive dysfunction. The global prevalence of NDs, including Alzheimer's disease, Parkinson's disease, Huntington's disease, and amyotrophic lateral sclerosis, is on the rise globally, primarily due to an aging population, positioning NDs as an increasing significant public health concern. Despite intensive research, few effective therapie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 261 publications
0
0
0
Order By: Relevance
“…6 In a recent communication, it has been reported that certain antidiabetic drugs of sulfonylurea class are extremely potent in inhibiting acetylcholinesterase (AChE) activity, suggesting their possible application in the treatment of Alzheimer's disease (AD). 7 Additionally, latest research findings from one of the present research groups indicate that tacrine (TAC), an FDA-approved AD medication, might also be effective in reversing the DNA oxidative stress caused by reactive oxygen species (ROS). 8,9 Intriguingly, in an earlier study, it is shown that the presence of graphene oxide (GO) enhances the anticholinergic effects of TAC, hinting at a synergistic interaction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 In a recent communication, it has been reported that certain antidiabetic drugs of sulfonylurea class are extremely potent in inhibiting acetylcholinesterase (AChE) activity, suggesting their possible application in the treatment of Alzheimer's disease (AD). 7 Additionally, latest research findings from one of the present research groups indicate that tacrine (TAC), an FDA-approved AD medication, might also be effective in reversing the DNA oxidative stress caused by reactive oxygen species (ROS). 8,9 Intriguingly, in an earlier study, it is shown that the presence of graphene oxide (GO) enhances the anticholinergic effects of TAC, hinting at a synergistic interaction.…”
Section: Introductionmentioning
confidence: 99%
“…This approach proved especially crucial in the initial phases of the COVID-19 outbreak, where the adaptation of existing medications played a key role in managing the critical health crisis by addressing various symptoms. Significant examples in this area include the discovery that inhibitors targeting leucine-rich repeat kinase 2 (LRRK2) might be effective for treating Parkinson’s disease (PD) . In a recent communication, it has been reported that certain antidiabetic drugs of sulfonylurea class are extremely potent in inhibiting acetylcholinesterase (AChE) activity, suggesting their possible application in the treatment of Alzheimer’s disease (AD) . Additionally, latest research findings from one of the present research groups indicate that tacrine (TAC), an FDA-approved AD medication, might also be effective in reversing the DNA oxidative stress caused by reactive oxygen species (ROS). , Intriguingly, in an earlier study, it is shown that the presence of graphene oxide (GO) enhances the anticholinergic effects of TAC, hinting at a synergistic interaction …”
Section: Introductionmentioning
confidence: 99%